2020
DOI: 10.1103/physrevb.102.104424
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy-induced depinning in the Zn-substituted skyrmion host Cu2OSeO3

Abstract: firhD wF F nd woodyD F rF nd ilsonD wF xF nd grisntiD wF nd fewleyD yF nd § tefn § i § D eF nd flkrishnnD qF nd pnD F nd tedmnD F nd el eneroD hF nd guittD F nd rttonD F hF @PHPHA 9enisotropyEindued depinning in the nEsustituted skyrmion host guPyeyQF9D hysil review fFD IHP @IHAF

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…2(e) and 2(f), we see that the magnitude of the peaks are reduced in the Ni-substituted sample. Similar behavior was previously reported in a Zn-substituted sample, where it was attributed to pinning effects introduced by the dopant [47]. Furthermore, there are two peaks seen in the ZFC data for both samples.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2(e) and 2(f), we see that the magnitude of the peaks are reduced in the Ni-substituted sample. Similar behavior was previously reported in a Zn-substituted sample, where it was attributed to pinning effects introduced by the dopant [47]. Furthermore, there are two peaks seen in the ZFC data for both samples.…”
Section: Resultssupporting
confidence: 87%
“…These have previously been attributed to the reorientation of different helical domains in the Cu 2 OSeO 3 when the field is applied along the [110]. Significantly, our data suggest that this reorientation occurs in both the Nisubstituted and pristine samples, while it has been reported that this feature is suppressed by Zn substitution [47]. This suggests that the magnetic Ni substitution modifies the phase transitions in Cu 2 OSeO 3 in a different manner compared to nonmagnetic Zn substitution.…”
Section: Resultssupporting
confidence: 54%
“…In particular, uniaxial anisotropy of the easy-axis type 65 , which does not affect the ideal single-harmonic type of the magnetization rotation in the conical spiral but just leads to the gradual closing of the cone, grants the thermodynamical stability of the V-SkL in a broad region of theoretical and experimental phase diagrams [66][67][68] . Cubic anisotropy also stabilizes V-SkLs but for specific directions of the applied magnetic field 38,[69][70][71] . This anisotropy deforms the ideal conical configuration as the magnetization tends to deviate from the ideal conical surface trying to embrace the easy axes and to avoid the hard directions.…”
Section: (B))mentioning
confidence: 99%
“…Unlike in the related compound FeGe, this change of sign does not induce a reorientation of the zero-field magnetic helix. This demonstrates that the 4 th order MCA also increases in magnitude with decreasing temperature, greater that the AEI in order to stabilize the zero-field magnetic helices along the 1 0 0 directions at all temperatures [37]. Our findings provide insight into the low temperature behavior of Cu 2 OSeO 3 that will be essential for complete understanding of the creation and stabilization mechanisms of the recently discovered LTS and TC phases within pristine Cu 2 OSeO 3 .…”
mentioning
confidence: 56%
“…A zinc-substituted sample was chosen for our study due to the reduction of the exchange interaction compared to pristine Cu 2 OSeO 3 , resulting in a greater value of q [37]. Previously, we have shown strong similarities of the magnetic behavior between Zn-substituted and pristine samples [37], and hence we expect our results here will extend to pristine samples. The time-of-flight neutron diffraction data was reduced with Mantid [40], using scattered neutron wavelengths between 0.9 and 13.5 A.…”
mentioning
confidence: 93%